Asia 2011-2015 - International Center for Tropical Agriculture (2011)
CIAT Asia’s research activities stretching back 30 years highlights significant research outcomes that have contributed to improve the livelihoods of many marginalized poor communities in the region. The current content and diversity of CIAT activities in Asia, the nature of its funding, and the major programmatic shifts within the Consultative Group on International Agricultural Research (CGIAR), provide an excellent opportunity to reconsider the future of CIAT research in Asia. The strategy is based on the assessment from the Center Commissioned External Review (CCER), consultations with partners in China, Vietnam, and Laos, and 6 months of internal discussion in CIAT. The strategic framework endorsed by the CIAT Board of Trustees has three major components: 1. Focus research on cassava and on forages for livestock systems, seeking a direct involvement with three forthcoming CGIAR Research Programs (CRPs): Roots and Tubers, Livestock and Fish, and Climate Change. 2. Increase the profile of research activities in tropical soil fertility particularly on cassava and forage systems with a direct link with two other forthcoming CRPs: Integrated Systems for the Humid Tropics and Water, Land and Ecosystems. 3. Strengthen the research capacity of CIAT and partners by achieving a critical mass of staff in the region, be they permanent, visiting, or seconded staff, by continuing to improve linkages with headquarters, and by refocusing staff management and funding approaches. With reallocation and hiring of new staff and exploration of new partnerships, the aim would be to achieve much stronger linkages with regional and national partners in emerging economies, such as Vietnam, Thailand, and China, which will translate into benefits for the region as a whole.